Temperature-dependent elastic properties of brain tissues measured with the shear wave elastography method. (January 2017) - Liu, Yan-Lin; Li, Guo-Yang; He, Ping; Mao, Ze-Qi; Cao, Yanping
Abstract: Determining the mechanical properties of brain tissues is essential in such cases as the surgery planning and surgical training using virtual reality based simulators, trauma research and the diagnosis of some diseases that alter the elastic properties of brain tissues. Here, we suggest a protocol to measure the temperature-dependent elastic properties of brain tissues in physiological saline using the shear wave elastography method. Experiments have been conducted on six porcine brains. Our results show that the shear moduli of brain tissues decrease approximately linearly with a slope of −0.041±0.006 kPa/°C when the temperature T increases from room temperature ( 23 °C) to body temperature ( 37 °C). A case study has been further conducted which shows that the shear moduli are insensitive to the temperature variation when T is in the range of 37 to 43 °C and will increase when T is higher than 43 °C. With the present experimental setup, temperature-dependent elastic properties of brain tissues can be measured in a simulated physiological environment and a non-destructive manner. Thus the method suggested here offers a unique tool for the mechanical characterization of brain tissues with potential applications in brain biomechanics research.